Main symptoms related to post-COVID syndrome, their reasons and physical therapy treatments (Research, Society and Development, 2023)
The present study is a narrative bibliographical review on persistent symptoms in the post-COVID period, aiming to generate understanding of such symptoms, thus showing the importance of physiotherapeutic rehabilitation programs. More than 200 symptoms are associated with post-COVID, thus weakening the quality of life of the individual affected by the disease, making simple tasks become complex as a result of the consequences of COVID-19. Post-COVID causes pathophysiological and systemic impairments, this study aims to identify the two main symptoms found in post-COVID, as well as understand the likely mechanism involved in the persistence of such symptoms, thus ensuring that physiotherapeutic rehabilitation programs are created with a focus on in the functional improvement of the affected individual. Wasserman and colleagues initially proposed a gear model that illustrated the integrated role of systems. Articles were analyzed which pointed out that the majority of people infected by COVID-19 present mild to moderate symptoms, and there are a portion of individuals who face the severe version of the disease and need hospital interventions. For these, the problems do not end when the virus disappears from the body, they present several symptoms with a greater predominance of fatigue and dyspnea, generated by deficits in several physiological systems. Such changes fit into the gear model that illustrates the role of the respiratory systems, cardiovascular and skeletal muscle. This finding is of fundamental importance for developing rehabilitation programs focused on improving the patient's ADL and full functional recovery.